2020
DOI: 10.3390/su12062489
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Set of Cooling Measures for the Overall Control and Reduction of High Temperature-Induced Thermal Damage in Oversize Deep Mines: A Case Study

Abstract: The mining process in deep mines occurs at elevated temperatures and thus is significantly jeopardized by the thermal damage. In this study, the main factors causing high-temperatures under particular mining geological and prevailing conditions of coal mine production, namely for the Longgu Coal Mine (LCM) in Shandong Province of China, were specified and analyzed in detail. This included exothermic heat from the surrounding rock of an underground roadway, inflow of high-temperature water, seasonal temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The rough element satisfies the fractal characteristics of statistical self-similarity, and the height h is proportional to the area of the bottom surface. 27 We assume constant C, then the total volume of the rough element in a fractal element can be obtained according to Equation (5).…”
Section: 𝜙 =mentioning
confidence: 99%
See 2 more Smart Citations
“…The rough element satisfies the fractal characteristics of statistical self-similarity, and the height h is proportional to the area of the bottom surface. 27 We assume constant C, then the total volume of the rough element in a fractal element can be obtained according to Equation (5).…”
Section: 𝜙 =mentioning
confidence: 99%
“…[1][2][3] The mining of deep coal resources will face a severe high-temperature environment, but at the same time, the geothermal resources contained in the deep can be used as symbiotic resources for mining and utilization. 4,5 The common problem involved is the heat transfer inside or between the coal rock mass and its exchange medium. 6 Therefore, establishing the relationship between pore structure and thermal conductivity is the key to clarifying the heat transfer of rock and even stratum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this area, the thermal effect mainly comes from the high-temperature airflow of the working face (Guo et al, 2017; Xu et al, 2022). Reducing the temperature of the airflow in the area is necessary to prevent the airflow of the working face from being heated (Zhang et al, 2020). Therefore, the study of heat transfer characteristics in production mines is an important factor and plays a vital role in controlling thermal hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Zhai et al [17] designed an LCO 2 circulating refrigeration system using the liquid carbon dioxide phase-change endothermic principle and used COMSOL Multiphysics software to simulate the heat transfer performance between CO 2 and airflow. The results showed that when the CO 2 consumption rate was 13.54 m 3 /h, the temperature of the airflow in the drift decreased by 7.72 • C. Zhang et al [18] used a mobile refrigeration unit, water source heat pump refrigeration unit, and ground centralized ice-cold radiation system to form a comprehensive refrigeration system. The integrated system reduced the average temperature of the main operating site by 8 • C and the average temperature of the underground working surface was kept below 26 • C. Tu et al [19] designed a free-cooling auxiliary air conditioning system that could significantly improve the annual average energy efficiency ratio of the system.…”
Section: Introductionmentioning
confidence: 99%